Full band Monte Carlo modeling of impact ionization, avalanche multiplication, and noise in submicron GaAs p[sup +]-i-n[sup +] diodes - Ong, D. S.; Li, K. F.; Plimmer, S. A.; Rees, G. J.; David, J. P. R.; Robson, P. N. (2000)
A full-band Monte Carlo model is used to investigate the probability distribution functions of impact ionization path length and impact ionization energy for electrons and holes in GaAs. The simulations show that the soft ionization threshold energy in GaAs allows impact ionization to occur at energies much higher than the band gap. As a result, secondary carriers have a shorter dead space than newly injected carriers. The ionization path length distributions narrow at higher fields, producing a more deterministic impact ionization process in thin devices. The model is also used to simulate avalanche multiplication and noise in submicron homojunction GaAs p(+)-i-n(+) diodes. The predicted mean multiplication, < M > and excess noise factor, F are in quantitative agreement with the experimental results, in which F decreases as the length of multiplication region is reduced. (C) 2000 American Institute of Physics. [S0021- 8979(00)08211-6].